Adsorption of l‐selenomethionine and l‐selenocystine on the surface of silver nanoparticles: A spectroscopic study. Issue 1 (16th October 2020) - Dhayagude, Akshay C.; Debnath, Anil K.; Joshi, Satyawati S.; Kapoor, Sudhir; Maiti, Nandita
Abstract: Adsorption behavior of the seleno‐amino acids viz. l ‐selenomethionine (SeMet) and l ‐selenocystine (SeCys) on the surface of Ag nanoparticles (NPs) was investigated by surface‐enhanced Raman scattering (SERS) and X‐ray photoelectron spectroscopy (XPS). The bare and functionalized Ag NPs were characterized by UV‐visible absorption, DLS, zeta‐potential measurements and TEM. The Raman spectrum supported by DFT computed spectrum of SeMet and SeCys suggested the existence of zwitterionic and diselenide (Se‐Se) forms in the crystalline state. The SERS study of SeMet and SeCys indicates that the zwitterionic and diselenide forms, respectively bind to the Ag NPs primarily through the Se atom. In case of SeCys,  cleavage of the Se‐Se bond occurs on the Ag NPs surface. SERS results; thus, established the active anchoring sites involved in binding for both seleno‐amino acids and XPS analysis confirmed that Se atom was the most active coordinating site with minor involvement of the carboxylate and amino groups. The SERS study of the seleno‐amino acids showed the possibility of change in orientation of SeMet on the Ag NPs surface with alteration in concentration, while no variation in orientation was observed for SeCys. In this study, sensing of the SeMet and SeCys down to 100 nM level was also achieved. Abstract : Preferential binding affinity of different anchoring sites; Se atom, carboxylate and protonated amino groups of l ‐selenomethionine (SeMet) and l ‐selenocystine (SeCys) towards Ag nanoparticles was investigated by SERS and XPS. Both the analysis indicated that Se atom is the most active coordinating site. SERS study of SeMet clearly confirmed the existence of zwitterion form on the Ag NPs surface. Sensing of both the amino acids down to 100 nM level was achieved.